2020
DOI: 10.1158/0008-5472.can-20-0503
|View full text |Cite
|
Sign up to set email alerts
|

Transient Activation of the Hedgehog-Gli Pathway Rescues Radiotherapy-Induced Dry Mouth via Recovering Salivary Gland Resident Macrophages

Abstract: Irreversible hypofunction of salivary glands is a common side effect of radiotherapy for head and neck cancer and is difficult to remedy. Recent studies indicate that transient activation of Hedgehog signaling rescues irradiation-impaired salivary function in animal models, but the underlying mechanisms are largely unclear. Here, we show in mice that activation of canonical Gli-dependent Hedgehog signaling by Gli1 gene transfer is sufficient to recover salivary function impaired by irradiation. Salivary gland … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 43 publications
6
44
0
Order By: Relevance
“…The present study showed that the phagocytic activity of SG macrophages was extremely weak; however, the gene expression pro le of SMG macrophages suggested that SG macrophages regulate gland development and functions in SGs. This view is partly supported by recent ndings indicating that murine SG macrophages allow the patrolling of tissue by tissue-resident memory CD8 + T cells for homeostatic organ surveillance 29 , and attenuate radiotherapy-induced dry mouth through the activation of the Hedgehog pathway 37 . The further characterization of SG macrophages is important for evaluating the contribution of SG macrophage subpopulations to SG homeostasis and to the pathology of SG dysfunctions and their therapeutic purposes.…”
Section: Discussionmentioning
confidence: 81%
“…The present study showed that the phagocytic activity of SG macrophages was extremely weak; however, the gene expression pro le of SMG macrophages suggested that SG macrophages regulate gland development and functions in SGs. This view is partly supported by recent ndings indicating that murine SG macrophages allow the patrolling of tissue by tissue-resident memory CD8 + T cells for homeostatic organ surveillance 29 , and attenuate radiotherapy-induced dry mouth through the activation of the Hedgehog pathway 37 . The further characterization of SG macrophages is important for evaluating the contribution of SG macrophage subpopulations to SG homeostasis and to the pathology of SG dysfunctions and their therapeutic purposes.…”
Section: Discussionmentioning
confidence: 81%
“…Although numerous pathological conditions (e.g., bacterial and viral infections, autoimmune diseases such as Sjögren’s syndrome, malignant tumors, or irradiation) may cause disorders of the head neck salivary glands, these diseases are all characterized by acute or chronic inflammatory changes arising from microvascular dysfunction ( 1 , 3 6 , 41 ). Immune cell accumulation in microvasculature and perivascular tissue as well as microvascular leakage are key components of inflammatory reactions ( 8 , 10 ) that are regulated by parenchymal sentinel cells such as tissue-resident macrophages ( 7 , 8 , 11 13 ). Targeting these events in the injured gland microvasculature might therefore represent a promising approach for the prevention and treatment of these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The extravasation of leukocytes is associated with enhanced microvascular permeability, which leads to edema formation, reduced oxygenation, and remodeling of the underlying tissue, thus representing hallmarks of the inflammatory response ( 10 ). These microvascular processes are critically regulated by parenchymal sentinel cells such as tissue-resident macrophages (TRMs), which maintain microvascular homeostasis in intact and inflamed salivary glands ( 7 , 8 , 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent papers demonstrated the fundamental role of resident macrophages in salivary glands to repair and restore salivary function after damage through the secretion of pro-repair factors [ 56 , 57 ].…”
Section: Pathogenetic Mechanismsmentioning
confidence: 99%